The Role of Remuneration In Improving Hospital Performance - Layli Rahmawati; Mardiati Nadjib (Publikasi Indonesia, 2023)
The management of the hospital business unit is unique because apart from being a business unit, the hospital business also has a social mission. However, the performance of this hospital is also influenced by the management of the hospital, one of which is remuneration. This study aims to determine the role of remuneration in improving hospital performance. This study uses a literature review research method, while the data collection technique is carried out by exploring journals and other information relevant to the study. The results show that remuneration policies play a role in building a solid work team, supporting business strategies in carrying out the hospital's vision and mission, improving service performance and hospital financial performance, spurring employee motivation to have a high commitment to work. Fulfill the rights and obligations of employees and hospitals, which has an impact on increasing Hospital performance and income.